The role of nurses in HIV/AIDS care in Intensive Care: an integrative review (Research, Society and Development, 2022)
Objective: to analyze the evidence available in the literature on the role of nurses in HIV/ AIDS care in the intensive care unit. Methodology: Integrative literature review, with data collection in February and March 2022, in the following databases: LILACS (Latin American and Caribbean Literature on Health Sciences), BDEnf, Medline and Pubmed with texts available in full, from the last ten years (2012 -2022) in English, Portuguese and Spanish with theguiding question: what is the nurse's role in HIV/AIDS care within the context of intensive care based on the prevention of diseases and health promotion? Results: Five articles were analyzed, two published in Brazil and three abroad. The main findings are related to nursing dimensioning, intensive care and health promotion to HIV/AIDS patients. Discussion: From the verification of the studies we developed two categories: Critical care in the context of the patient with HIV-related disease and application of promotion and prevention of diseases in intensive care and its repercussions on the infection. Conclusion: Thus, this study has the function of opening a new front for discussion about patients admitted to intensive care units in the context of HIV/AIDS and nursing care in the face of this condition.